Investigation on SiCf / SiC Composites with SiBN Interface Processed through Chemical Vapor Infiltration. (2016) - Sathiyamoorthy, R.; Soorya Prakash, K.; Sathishkumar, C.; Gopal, P.M.
Abstract: The unidirectional Hi-Nicalon type-S fiber/SiC composites were fabricated by chemical vapor infiltration method and their microstructure, mechanical properties were examined. Borosilicate nitride interface coating was given to SiC fibers through low-pressure chemical vapor infiltration technique. Observations illustrate that specimen tensile strength initially increases and then decreases with increase in SiBN thickness achieving a maximum value of 90.6 MPa for the composite with 1000nm interface. Higher interface thickness increases the brittleness which results in decreased tensile properties. The temperature resistance characteristics of SiCf /SiC composites with SiBN interface were found to be stable at a maximum temperature of 1906.2°C.